Work process in urgent and emergency hospital: health impacts within the community of nurses (Research, Society and Development, 2020)
Objective: to identify scientific evidence regarding the relationship between work in urgency and emergency and the illness of nurses. Method: This is an integrative review, which carefully followed the six recognized stages. The research being carried out in virtual libraries and databases, during the second quarter of 2019. using the Health Sciences and Medical Subject Headings (Decs / MeSH) Descriptors: Nurse; Emergency nursing; Professional Exhaustion, in its English versions, associated through the Boolean operator AND to the aforementioned descriptors.  Results: make it evident that the urgency and emergency sector requires greater dedication from the nursing professional, resulting in stressful situations, and important challenges related to the health risks inherent to the patient's condition. Such a routine interferes with the worker's life, ranging from routine stress to pain as a physical sign of exhaustion or injuries as a result of this exhausting work. Conclusions: It points to the different meanings of nurses' exposure to stressful environments, which generate anxieties, which are hospital urgencies and emergencies.